2005
DOI: 10.1038/sj.ijo.0803096
|View full text |Cite
|
Sign up to set email alerts
|

Mini Review: Physical activity and fitness and its relations to cardiovascular disease risk factors in children

Abstract: OBJECTIVES: This paper aim to review the newest literature linking physical inactivity and low fitness to metabolic disorders including cardiovascular disease (CVD) risk factors and obesity. METHODS: There is a rationale for early prevention of CVD if (a) children have a risk factor profile, where risk for future disease is increased, (b) physical activity and CVD risk factors track into adulthood, and (c) increased physical activity can improve the risk factor profile. We reviewed the evidence for a progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
78
1
11

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 70 publications
7
78
1
11
Order By: Relevance
“…Wareham et al (3) reviewed 12 such studies relating habitual physical activity to insulin resistance and found five that reported a weak-to-moderate correlation. Froberg and Andersen (4) reported similar findings with studies measuring physical activity and lipids, in which five reported no association and the remaining six a weak association. The same authors also reported six studies in which the relationship between physical activity and blood pressure was investigated: three showed an association and three did not.…”
supporting
confidence: 72%
“…Wareham et al (3) reviewed 12 such studies relating habitual physical activity to insulin resistance and found five that reported a weak-to-moderate correlation. Froberg and Andersen (4) reported similar findings with studies measuring physical activity and lipids, in which five reported no association and the remaining six a weak association. The same authors also reported six studies in which the relationship between physical activity and blood pressure was investigated: three showed an association and three did not.…”
supporting
confidence: 72%
“…Thorough reviews have recently discussed the associations between physical activity at young ages and its short/long-term consequences on health. [5][6][7][8][9][10] However, less is known about physical fitness and health outcomes in young people. 9 In the last years, an increasing amount of research on physical fitness and health in childhood and adolescence has been published.…”
Section: Introductionmentioning
confidence: 99%
“…Beispielsweise haben körper-lich aktive Kinder ein günstigeres kardiovaskuläres Risikoprofil und eine höhe-re Knochendichte, sind seltener überge-wichtig und haben ein besseres psychisches Wohlbefinden [1][2][3][4][5][6][7]. Körperliche Inaktivität, insbesondere in Zusammenhang mit Bildschirmmediennutzung, ist hingegen mit der Entstehung von Über-gewicht assoziiert [8][9][10].…”
unclassified